ANALISIS PENERAPAN AKAD MURABAHAH DAN WAKALAH BIL UJRAH PADA INVESTASI EMAS DIGITAL - Milatun Nafiah; Ani Faujiah (Jurnal Ekonomi Syariah Darussalam, 2025)
Digitalization of gold transactions triggers sharia compliance debates on ribawi commodities. This qualitative library research (2021–2026) aims to analyze the integration of murabahah and wakalah bil ujrah contracts, evaluate taqabudh hukmi fulfillment, and examine the implications of PSAK 102 on digital gold platforms. The results indicate that Murabahah and Wakalah bil Ujrah contracts integrate independently without ta'alluq, provided the platform offers physical withdrawal flexibility from the start. The taqabudh hukmi aspect is fulfilled through digital constructive possession (takhliyah) backed 100% by physical gold in the custodian vault to avoid fictitious sales (bai' ma'dum), weight precision, and a physical withdrawal option. Furthermore, PSAK 102 effectively acts as a sharia filter through real-time full disclosure of cost prices and profit margins. This study recommends refining the application's user interface to ensure user freedom of choice (ikhtiyar) and stresses the need for cross-sectoral regulatory harmonization for regular cyber technology audits.